2017
DOI: 10.3389/fcell.2017.00022
|View full text |Cite
|
Sign up to set email alerts
|

Non-myogenic Contribution to Muscle Development and Homeostasis: The Role of Connective Tissues

Abstract: Skeletal muscles belong to the musculoskeletal system, which is composed of bone, tendon, ligament and irregular connective tissue, and closely associated with motor nerves and blood vessels. The intrinsic molecular signals regulating myogenesis have been extensively investigated. However, muscle development, homeostasis and regeneration require interactions with surrounding tissues and the cellular and molecular aspects of this dialogue have not been completely elucidated. During development and adult life, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 167 publications
1
100
0
Order By: Relevance
“…The tendons are the tensional links between the bones and muscles. The muscle connective tissue (MCT, sometimes called dense irregular connective tissue; Nassari et al, 2017) is the muscle’s closest anatomical and functional partner (Figure 2B). MCT is composed of three layers: the endomysium ensheathes individual myofibers, the perimysium bundles myofibers into fascicles, and the epimysium surrounds anatomical muscles and links to the tendons at the myotendinous junctions (Sanes, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tendons are the tensional links between the bones and muscles. The muscle connective tissue (MCT, sometimes called dense irregular connective tissue; Nassari et al, 2017) is the muscle’s closest anatomical and functional partner (Figure 2B). MCT is composed of three layers: the endomysium ensheathes individual myofibers, the perimysium bundles myofibers into fascicles, and the epimysium surrounds anatomical muscles and links to the tendons at the myotendinous junctions (Sanes, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Since embryonic Osr1+ cells have been explicitly shown to give rise to FAPs (Vallecillo-García et al, 2017) and most adult MCT fibroblasts express Tcf4 and PDGFRα and activated FAPs express Osr1 (Murphy et al, 2011; Stumm et al, 2018; Uezumi et al, 2010), MCT fibroblasts and FAPs are likely the same cell population. However, molecular heterogeneity and sub-populations within these fibroblasts undoubtedly exist (also see discussions in Nassari et al, 2017; Wosczyna and Rando, 2018). …”
Section: Introductionmentioning
confidence: 99%
“…A broad range of prior investigations have revealed that cranial neural crest mesenchyme plays a critical role during muscle development. In particular, the early migration, differentiation, and spatial patterning of myogenic mesenchyme in the head relies on interactions with surrounding muscle connective tissues (Borue & Noden, 2004;Ericsson, Cerny, Falck, & Olsson, 2004;Francis-West et al, 2003;Grammatopoulos et al, 2000;Grenier, Teillet, Grifone, Kelly, & Duprez, 2009;Hall, 1950;Knight, Mebus, & Roehl, 2008;Knight & Schilling, 2006;Köntges & Lumsden, 1996;McGurk et al, 2017;Nassari, Duprez, & Fournier-Thibault, 2017;Noden, 1983Noden, , 1986aNoden, , 1988Noden, Marcucio, Borycki, & Emerson, 1999;Noden & Schneider, 2006;Noden & Trainor, 2005;Olsson, Falck, Lopez, Cobb, & Hanken, 2001;Pasqualetti et al, 2000;Rinon et al, 2007;Schilling et al, 1996;Schnorrer & Dickson, 2004;Subramanian & Schilling, 2015;Sugii et al, 2017;Tokita, Nakayama, Schneider, & Agata, 2013;Trainor & Krumlauf, 2000;Trainor, Sobieszczuk, Wilkinson, & Krumlauf, 2002;Tzahor et al, 2003).…”
Section: Origin Of Species-specific Pattern In the Jaw Musculaturementioning
confidence: 99%
“…Muscle connective tissue fibroblasts regulate muscle morphogenesis by establishing a prepattern for the muscle that the migrating myoblasts follow (Jacob et al, 1979;Chevallier and Kieny, 1982;Kardon, 1998;Kardon et al, 2003;Nassari et al, 2017). In conjunction, connective tissue fibroblasts contribute to the tendons, which mediate muscle-to-bone attachment at their origin and insertion and provide boundaries for muscle formation (Kardon, 1998).…”
Section: Bbds Mutations Alter Musculoskeletal Integration In the Chicmentioning
confidence: 99%